Adherence to European Society of Cardiology Heart Failure Treatment Guideline in Haji Adam Malik General Hospital Medan - Wirtanto, Ardy Putra; Sitepu, Andika (Sumatera Medical Journal, 2020)
Background. Heart failure is a public health problem and the main cause of morbidity and mortality in the world. The goal of the therapy is to reduce symptoms, prevents rehospitalization and increases survivability. Objective. To evaluate the adherence to the European Society of Cardiology for heart failure treatment at H. Adam Malik Medan hospital. Methods. The study was descriptive observational cross sectional design with medical record data of heart failure at H. Adam Malik Hospital, using consecutive sampling method. The adherence of guidelines was assessed by: (1) drug prescribing (“yes” or “no”), and (2) guideline adherence indicator (GAI), both GAI-3 or GAI-5, by calculating the proportion as the number of drugs prescribed by number of drugs indicated to the ESC guidelines. Results. From research, the predominant GAI-3 and GAI-5 were High, which were 54.9% and 59.5%, respectively. The recommended drug used based on indications were ACE-i / ARB (89.1%), beta-blockers (83.4%), MRA (73.6%), diuretics (93.7%), and digitalis (20,8%). Conclusion. The predominant category in adherence to the ESC heart failure treatment guidelines based on GAI-3 and GAI-5 is High.